EFEKTIVITAS APLIKASI MACAM PUPUK ORGANIK CAIR DAN VARIETAS TERHADAP PENINGKATAN PRODUKSI SAWI (Brasica juncea L.)YANG DIBUDIAYAKAN SECARA HIDROPONIK - Dian Eka Kusumawati; Ferry Nurdiansyah; Choirul Anam (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2021)
Mustard (Brassica juncea L.) is one of the most popular horticultural commodities. So it is necessary to increase the production of mustard plants by hydrophonic and using liquid organic fertilizer (LOF). In the hydroponic system, growth and development is very dependent on providing nutrients. The research was conducted in the village of Gampangsejati, Laren District, Lamongan Regency. The time of the study was carried out in February 2021 to June 2021. The study was carried out in a non-greenhouse. The study was conducted using a factorial randomized block design method which consisted of 3 levels, namely for factor 1 the fertilizer treatment used was AB Mix Nutrition, cow biourine LOF and goat manure LOF. Factor 2 varieties used are Sawi nauli, Sawi shinta and Sawi green. The results of the research that have been carried out are that the use of AB mix treatment showed the best growth and yield of mustard shinta, mustard nauli and mustard green plant varieties compared to cow biourine LOF and goat dung LOF treatments.